Kilertinguak 2000 m Umanatsiak bei Ikerasak, Umanak, Stor-Ö - Heim, Arnold (ETH-Bibliothek Zürich, Bildarchiv, 1909)
Download und Nutzung frei : 02:30 p.m. From the left: Kilertinguak (Qilertinnguaq), Umanatsiak Berg (Uummannatsiaq), Umanak Berg (Uummannaq), Stor-Ö